Probing near Dirac point electron-phonon interaction in graphene - Gurzadyan, Gagik G. (2013)
Carrier dynamics in graphene films on CaF2 have been measured in the mid infrared region by femtosecond pump-probe spectroscopy. The relaxation kinetics shows two decay times. The fast time component is ~0.2 ps, which is attributed to the mixture of initial few ultrafast intraband and interband decay channels. The slow component is ~1.5 ps, which is primarily assigned to optical phonon-acoustic phonon scattering. The contribution of fast component exhibits an increase trend in the probe photon frequencies from 2600 to 3100 cm−1. At the probe frequency of 2700 cm−1, the accelerated carrier relaxation was detected, which resulted from the interband triple-resonance electron-phonon scattering in graphene. At the probe frequency of 3175 cm−1, a clear instant negative differential transmission signal was observed, which is due to stimulated two-phonon emission involved with G phonons in graphene. This result indicates that graphene can be used as a source of coherent ultrashort sound-wave emission.